What Drives Corporate Social Responsibility Disclosure? Evidence from Indonesian Manufacturing Firms - Ni Putu Ayuni Candra Dewi; Putu Wenny Saitri; Ni Wayan Rustiarini (JUSTBEST Journal of Sustainable Business and Management, 2026)
Corporate social responsibility (CSR) disclosure has become an increasingly important aspect of corporate transparency, particularly in industries with significant social and environmental impacts. However, empirical evidence regarding the determinants of CSR disclosure remains inconclusive, especially in emerging markets such as Indonesia. This study examines the influence of profitability, consumer proximity, media exposure, environmental sensitivity, and tax aggressiveness on CSR disclosure among manufacturing companies listed on the Indonesia Stock Exchange during 2020–2022. Using purposive sampling, this study resulted in 297 firm-year observations. Data were analyzed using multiple linear regression after classical assumption tests were conducted. The findings reveal that media exposure and tax aggressiveness have a significant positive effect on CSR disclosure, suggesting that companies tend to increase transparency of social responsibility to enhance public communication and maintain legitimacy amid potentially controversial fiscal practices. In contrast, profitability, consumer proximity, and environmental sensitivity do not significantly affect CSR disclosure. These findings indicate that CSR disclosure in Indonesian manufacturing firms is driven more by reputational concerns and external communication pressures than by financial capability or operational characteristics. This study contributes to the CSR literature by integrating financial performance, stakeholder visibility, industry characteristics, and fiscal behavior into a single empirical framework. By examining these multidimensional determinants simultaneously in Indonesian manufacturing firms, the study provides a more comprehensive understanding of the factors driving CSR disclosure in an emerging market setting.